2017
DOI: 10.1007/s40615-017-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Racial Inequities at the End of Life: A Call for Health Systems to Create Culturally Competent Advance Care Planning Programs Within African American Communities

Abstract: Racial and cultural barriers inherent in health systems have made the delivery of culturally relevant end of life care that aligns with patient preferences a particular challenge across African American patient populations. The end of life experience has been cited as a public health crisis by the Institute of Medicine (IOM), and this crisis is one felt even more acutely by patients of this minority race. Structural racism has limited access to the planning mechanisms proven to result in quality end of life ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Additionally, insufficient communication could cause providers to not fully understand patients’ needs and order unnecessary treatments or tests , which may help explain the results of our analysis of pharmacy/drug and laboratory costs. Regarding the inequality of treatment among minority groups, Belisomo (2018) pointed out that structural racism existed in end‐of‐life care and that providing advance care planning that is culturally attentive would help to alleviate this issue .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, insufficient communication could cause providers to not fully understand patients’ needs and order unnecessary treatments or tests , which may help explain the results of our analysis of pharmacy/drug and laboratory costs. Regarding the inequality of treatment among minority groups, Belisomo (2018) pointed out that structural racism existed in end‐of‐life care and that providing advance care planning that is culturally attentive would help to alleviate this issue .…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 40 years ACP initiatives have had greater visibility. However, health care systems were not successful in promoting ACP among African American adults,1 specifically the completion of an advance directive (AD) document, with AD completion rates for African American adults ranging from 0% to 47.3% 2–5…”
Section: Background and Objectivesmentioning
confidence: 99%
“…10 Even when information is provided in the patient's language, lack of cultural adaptation may impair adequate communication in palliative care and hospice education materials. 14,[16][17][18][19] Underserved communities within the US also share a trend to mistrust healthcare providers, and minority patients at the end-of-life may harbor suspicions that healthcare providers may not be acting in the best interest of the patient. 14,20 However, this assumption has been strongly challenged by the findings of at least one study, 21 where authors reported that minority patients, those with lower income and those with high religiosity/spirituality rated trust in clinician communications higher than populations not sharing these characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…10 Even when information is provided in the patient’s language, lack of cultural adaptation may impair adequate communication in palliative care and hospice education materials. 14,16-19…”
Section: Introductionmentioning
confidence: 99%